2022
DOI: 10.1016/j.csbj.2021.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Imaging flow cytometry reveals a dual role for exopolysaccharides in biofilms: To promote self-adhesion while repelling non-self-community members

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Next, we explored whether a difference in bacillaene production underlies the reduced inhibition by B. subtilis in nutrient-depleted conditions. Here, we measured the expression of the pks operon via a P pksC - yfp reporter fusion in nutrient-rich and nutrient-depleted conditions, since it has been previously established that activity of the P pksC promoter correlates well with bacillaene synthesis ( 45 , 46 ). In addition, because it has been shown that bacteria can alter the production of antimicrobials in the presence of competitors ( 45 , 47 , 48 ), we compared the expression between monoculture and coculture conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we explored whether a difference in bacillaene production underlies the reduced inhibition by B. subtilis in nutrient-depleted conditions. Here, we measured the expression of the pks operon via a P pksC - yfp reporter fusion in nutrient-rich and nutrient-depleted conditions, since it has been previously established that activity of the P pksC promoter correlates well with bacillaene synthesis ( 45 , 46 ). In addition, because it has been shown that bacteria can alter the production of antimicrobials in the presence of competitors ( 45 , 47 , 48 ), we compared the expression between monoculture and coculture conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that biofilm formation could alter the production of bacillaene and mediate the outcome of interspecies interactions ( 46 ). The extracellular matrix of the B. subtilis biofilm is composed of polysaccharides, proteins, and nucleic acids ( 27 , 40 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant of Lactiplantibacillus plantarum affects glucose metabolism and inhibits the expression of the virulence gene of C. albicans, which encodes an agglutinin-like protein [37]. Maan et al [38] discovered that EPS provides dual adaptive advantages for cells to form biofilms, which not only promote the co-aggregation of related species, but also inhibit the growth of incompatible species.…”
Section: Formation and Maturation Of Microcoloniesmentioning
confidence: 99%
“…Colony forming units (CFUs) were then counted after the 20-hour growth curve using the resultant culture as described in Maan et al 50 Briefly, the culture was transferred to a 96-well plate and a serial dilution from 10 0 to 10 -7 was performed in DPBS. 20 µL of varying dilutions were spotted onto LB agar plates and allowed to dry completely in clean bench hood.…”
Section: Analysis Of the Swelling Capacity Of Hydrogelsmentioning
confidence: 99%